Positive pole piece, battery, energy storage device and electric equipment
By using secondary particles formed of the third particles in the positive electrode sheet, a plurality of step-like structures with a high tendency to decrease are formed, the problem of high ductility of the positive electrode sheet is solved, and the capacity performance of the lithium-ion battery and the service life of the energy storage device are improved.
Patent Information
- Application Number
- CN202510109951.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-23
AI Technical Summary
While increasing the capacity of lithium-ion batteries, the ductility of the positive electrode sheet becomes higher, affecting the stability and service life of the battery.
By using secondary particles formed of the third particles in the positive electrode sheet, multiple step-like structures with a high tendency to decrease are formed, the roughness of the particle surface is increased, the deformation and slip of the particles are prevented, and the electrolyte is immersed through the gaps is promoted, and the Li+ diffusion ability is improved.
It reduces the ductility rate of the positive electrode sheet, improves the capacity performance of lithium-ion batteries, and extends the service life of the energy storage device.
Smart Images

Figure CN119905516A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a positive electrode sheet, a battery, an energy storage device and an electrical equipment. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight. They are widely used in various fields such as energy storage, portable electronic devices and electric vehicles.
[0003] Lithium-ion batteries based on lithium iron phosphate positive electrode materials have the advantages of high safety and stability. With the increasing demand for battery capacity in energy storage scenarios, lithium iron phosphate materials with smaller particle sizes are often used, but this leads to the problem of higher elongation of the positive electrode during rolling. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a positive electrode sheet, a battery, an energy storage device and an electrical equipment, which can improve the capacity performance of the secondary battery while reducing the elongation rate of the positive electrode sheet.
[0005] In a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector, wherein at least one side of the positive electrode current collector has a positive electrode material layer, wherein the positive electrode material layer comprises a positive electrode material, wherein the positive electrode material comprises a first particle and a second particle, wherein the second particle is a secondary particle formed by a third particle, and the first particle and the third particle are primary particles;
[0006] Wherein, along the longest diameter of the second particle and in the direction away from the center of the second particle, the third particles located on the surface of the second particle form a plurality of step-like structures with decreasing height, and the plurality of step-like structures have gaps;
[0007] A ratio of the surface area of the second particle to the area of the maximum cross section of the second particle is A, 3≤A≤10.
[0008] In some embodiments of the present application, the average particle size of the third particles located on the surface of the second particles is d1, and 1 μm≤d1≤3 μm.
[0009] In some embodiments of the present application, the Dv50 of the positive electrode material is 1 μm to 3 μm.
[0010] In some embodiments of the present application, one of the step-like structures is formed by fusion of a plurality of the third particles, and the gap is located at the fusion interface.
[0011] In some embodiments of the present application, the gap is located at the junction of adjacent step-like structures.
[0012] In some embodiments of the present application, the positive electrode material has a chemical formula of LiFe x Ti y PO4 / C, x+y=1, and 0<y≤0.05.
[0013] In some embodiments of the present application, the elongation of the positive electrode sheet is 0.5% to 2.3%.
[0014] In a second aspect, the present application provides a battery, comprising the positive electrode plate described in the first aspect.
[0015] In a third aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the second aspect, wherein the battery is accommodated in the housing.
[0016] In a fourth aspect, the present application provides an electrical device, comprising the energy storage device described in the third aspect, wherein the energy storage device supplies power to the electrical device.
[0017] Compared with the prior art, this application has at least the following beneficial effects:
[0018] The present application provides a positive electrode sheet, a battery, an energy storage device and an electrical device, wherein the positive electrode sheet comprises a positive electrode current collector, at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer comprises a positive electrode material, the positive electrode material comprises a first particle and a second particle, the second particle is a secondary particle formed by a third particle, wherein the third particle located on the surface of the second particle forms a plurality of step-like structures with a decreasing height trend along the longest diameter of the second particle and away from the center of the second particle, so that the surface of the second particle achieves a roughness far greater than that of ordinary lithium iron phosphate material particles; the ratio of the surface area of the second particle to the area of the maximum cross section of the second particle is A, 3≤A≤10, which is conducive to preventing the deformation and slippage of the particle when under pressure and reducing the elongation rate of the positive electrode sheet; and the plurality of step-like structures have gaps, which can promote the rapid infiltration of the electrolyte into the second particle through these gaps, thereby improving Li + In summary, the present invention can improve the capacity performance of the secondary battery while reducing the elongation rate of the positive electrode sheet, which is beneficial to improving the capacity and service life of the energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 A schematic diagram of a second particle according to an embodiment of the present application;
[0021] Figure 2 A schematic diagram of a step-like structure in a second particle according to an embodiment of the present application;
[0022] Figure 3 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;
[0023] Figure 4 A schematic diagram of the structure of a commercial energy storage system according to an implementation scheme of the present application;
[0024] Figure 5 A schematic diagram of the elongation test of the positive electrode sheet of this application;
[0025] Figure 6 This is a scanning electron microscope (SEM) image of the positive electrode material of Example 1 (magnification is 10,000 times);
[0026] Figure 7 This is a SEM image of the positive electrode material of Example 1 (magnification is 30,000 times);
[0027] Figure 8 This is a SEM image of the positive electrode material of Comparative Example 1 (magnification is 10,000 times);
[0028] Fig. 9 This is the SEM image of the positive electrode material of Comparative Example 1 (magnification is 30,000 times).
[0029] Explanation of the accompanying drawings: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-step-like structure, 40-roller, 101-first step-like structure, 102-second step-like structure, 103-third step-like structure, 1021-third particle, 400-commercial energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0031] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0032] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0033] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0034] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0035] It should be noted that, in the content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0036] The present application provides a positive electrode sheet, which includes a positive electrode current collector, at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, the positive electrode material includes a first particle and a second particle, the second particle is a secondary particle formed by a third particle, and the first particle and the third particle are primary particles. The material type of the first particle and the second particle can be the same, for example, both are lithium iron phosphate materials. Reference Figure 1In the cross section of the second particle, along the longest diameter D of the second particle and in the direction away from the center O of the second particle (the direction of the arrow shown in the figure), the third particle located on the surface of the second particle forms a plurality of step-like structures 10 with a decreasing height, and the plurality of step-like structures have gaps; the ratio of the surface area of the second particle to the area of the maximum cross section of the second particle is A, 3≤A≤10. For example, A=3, A=6, A=7, A=9 or A=10.
[0037] The positive electrode sheet of the present application contains the above-mentioned positive electrode material, wherein the multiple step-like structures with a decreasing height trend can make the surface of the second particle achieve a roughness far greater than that of ordinary lithium iron phosphate material particles, making the positive electrode material less likely to deform and slip when under pressure; the inventors have found that when the A value is too small (for example, less than 3), the shape of the second particle is more inclined to present a spherical structure, which is more likely to be displaced and deformed during rolling, which is not conducive to reducing the elongation of the positive electrode sheet; when the A value is too large (for example, greater than 10), the roughness of the second particle is too high, and the positive electrode material is less likely to deform and slip when under pressure, and the elongation of the positive electrode sheet is significantly reduced, but due to the increase in the gaps between the particles, the compaction of the positive electrode sheet is reduced, thereby reducing the capacity of the energy storage device. The present application is beneficial to hindering the deformation and slippage of the particles when under pressure and reducing the elongation of the positive electrode sheet by regulating the A value within the above range. In addition, the multiple step-like structures in the second particle have gaps, which can promote the rapid infiltration of the electrolyte into the interior of the second particle through these gaps, thereby increasing Li + In summary, the present invention can improve the capacity performance of lithium-ion batteries while reducing the elongation rate of the positive electrode sheet, which is beneficial to improving the capacity and service life of the energy storage device.
[0038] In the present application, the area of the maximum cross section of the second particle refers to randomly selecting 50 second particles, calculating the area of the cross section of each particle, and taking the area of the maximum cross section as the recorded value.
[0039] In an optional embodiment, the average particle size of the third particles located on the surface of the second particles is d1, 1μm≤d1≤3μm. For example, d1=1μm, d1=1.5μm, d1=2μm or d1=3μm. By adjusting d1 within the above range, it is beneficial to form the above-mentioned multiple step-like structures with a decreasing height trend of the unevenness, thereby increasing the roughness of the surface of the second particles.
[0040] In an optional embodiment, the Dv50 of the positive electrode material is 1 μm to 3 μm. For example, the Dv50 of the positive electrode material is 1 μm, 2 μm or 3 μm. By adjusting the Dv50 of the positive electrode material within the above range, it is beneficial to make the positive electrode material have a higher compaction density, thereby improving the performance of the capacity performance of the positive electrode material.
[0041] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in a volume-based particle size distribution of particles.
[0042] In an optional embodiment, a step-like structure is formed by fusion of multiple third particles, and the gap is located at the fusion interface, which is conducive to the electrolyte entering the second particles through these gaps, improving the electrolyte wettability of the second particles, thereby improving the capacity performance of the positive electrode material. Figure 2 , showing three stepped structures with decreasing heights, namely, a first stepped structure 101, a second stepped structure 102, and a third stepped structure 103. Taking the second stepped structure 102 as an example, the second stepped structure 102 shows four fused third particles 1021, and the gap can be located at the fusion interface of the third particles 1021, and the third particles 1021 are a primary particle.
[0043] In an optional embodiment, the gap is located at the junction of adjacent step-like structures, which is conducive to the electrolyte entering the second particles through these gaps, improving the electrolyte wettability of the second particles, thereby improving the capacity performance of the positive electrode material. Figure 2 For example, the gap may be located at the junction of the first stepped structure 101 and the second stepped structure 102 , and / or the gap may be located at the junction of the second stepped structure 102 and the third stepped structure 103 .
[0044] In an alternative embodiment, the positive electrode material has the chemical formula LiFe x Ti y PO4 / C, x+y=1, and 0<y≤0.05. For example, y=0.01, 0.02, 0.03, 0.04 or 0.05. The positive electrode material having the above chemical formula contains doping element titanium (Ti), which can provide more capacity and is conducive to improving the capacity performance of lithium-ion batteries.
[0045] In an optional embodiment, the elongation of the positive electrode sheet is 0.5% to 2.3%; in another optional embodiment, the elongation of the positive electrode sheet is 0.5% to 1.6%. For example, the elongation of the positive electrode sheet is 0.5%, 0.8%, 1.0%, 1.3%, 1.6% or 2.3%. A lower elongation is beneficial to reduce the risk of cracking at the edge of the positive electrode sheet and improve the yield of the lithium-ion battery.
[0046] In an optional embodiment, the method for preparing the positive electrode material comprises the following steps:
[0047] Step A: Preparation of the first precursor material:
[0048] Step a: According to LiFex Ti y The iron source, phosphorus source, lithium source, titanium source and carbon source are weighed in the required stoichiometric ratio of PO4 / C (x+y=1, and 0<y≤0.05), uniformly mixed on a ball mill, and then an appropriate amount of pure water is added as a dispersant, and then high-energy ball milling is performed;
[0049] Step b, spray drying the material after high-energy ball milling to form granular powder;
[0050] Step c: placing the granular powder into a vacuum atmosphere sintering furnace for a first sintering treatment, and then crushing the powder to obtain a first precursor material.
[0051] In step a, the iron source can be selected from ferrous oxalate, ferric phosphate or ferric oxide, the phosphorus source can be selected from lithium dihydrogen phosphate or ammonium dihydrogen phosphate, the lithium source can be selected from lithium carbonate or lithium hydroxide, the titanium source is selected from titanium dioxide, and the carbon source can be selected from glucose, sucrose or citric acid; the ball-to-material ratio of the high-energy ball mill is 3 to 5:1, the rotation speed is 1000 r / min to 2000 r / min, and the ball milling time is 15 h to 20 h.
[0052] In step b, the pump speed of spray drying is 8 mL / min to 12 mL / min, the drying temperature is 180° C. to 220° C., and the formed powder is granular.
[0053] In step c, the protective atmosphere is nitrogen, the temperature of the first sintering treatment is 380° C. to 420° C., and the sintering time is 5 h to 10 h.
[0054] Step B: Preparation of the second precursor material:
[0055] Step a', according to LiFe x Ti y Weigh an iron source, a phosphorus source, a lithium source, a titanium source and a carbon source in the required stoichiometric ratio of PO4 / C (x+y=1, and 0<y≤0.05), mix them to obtain a mixed metal salt solution, and then prepare a strong base solution as a precipitant solution and an ammonia solution as a complexing agent solution;
[0056] Step b', placing the mixed metal salt solution, complexing agent solution and precipitant solution prepared above in a reaction kettle, stirring continuously, maintaining the pH value of the reaction liquid at 9±0.5, the reaction temperature at 180°C to 200°C, the reaction time at 8h to 10h, synthesizing by precipitation reaction, and obtaining a second precursor material after solid-liquid separation, washing and drying.
[0057] In step a', the iron source can be selected from ferrous oxalate, ferrous sulfate or ferric chloride, the phosphorus source can be selected from phosphoric acid or diammonium phosphate, the lithium source can be selected from lithium carbonate or lithium hydroxide, the titanium source can be selected from titanium tetrachloride, and the carbon source can be selected from glucose, sucrose or citric acid; the above raw materials can be first prepared into corresponding solutions, and then the solutions containing the above raw materials are mixed to obtain a mixed metal salt solution, wherein the molar concentration of titanium in the mixed metal salt solution is 0.3 mol / L to 0.7 mol / L; the strong alkaline solution can be a sodium hydroxide solution with a molar concentration of 0.5 mol / L to 1 mol / L, and the molar concentration of ammonia water is 0.5 mol / L to 1.5 mol / L. The solvent in the mixed metal salt solution in the present application can include water.
[0058] In step b', a complexing agent may be first added to the mixed metal salt solution to adjust the pH value to 9±0.5, and then a precipitant solution may be added. As the precipitate is generated, the complexing agent may be continuously added to adjust the pH value to maintain at 9±0.5. This process is a precipitation reaction process.
[0059] Step C: Preparation of positive electrode material:
[0060] The first precursor material and the second precursor material are mixed to obtain a pre-burned material, wherein the mass percentage of the second precursor material in the pre-burned material is 10% to 50%, preferably 20% to 50%; the pre-burned material is then placed in a vacuum atmosphere sintering furnace for a second sintering treatment, and then crushed to obtain a positive electrode material, wherein the protective atmosphere is nitrogen, the temperature of the second sintering treatment is 700°C to 800°C, preferably 700°C to 780°C; the sintering time is 10h to 20h, preferably 10h to 18h.
[0061] The present application has no particular restrictions on the method of regulating the ratio of the surface area of the second particle to the area of the maximum cross-section of the second particle (the A value), as long as the purpose of the present application can be achieved. For example, the A value usually decreases with the increase of the content of the second precursor material in the pre-sintered material. Based on this, the present application can regulate the A value by regulating the content of the second precursor material in the pre-sintered material; for another example, the A value usually decreases with the increase of the sintering temperature of the second sintering treatment. Based on this, the present application can regulate the A value by regulating the sintering temperature of the second sintering treatment; for another example, the A value usually decreases with the increase of the sintering time of the second sintering treatment. Based on this, the present application can regulate the A value by regulating the sintering time of the second sintering treatment.
[0062] The present application has no particular restrictions on the method of regulating d1, as long as the purpose of the present application can be achieved. For example, d1 usually increases with the increase of the content of the second precursor material in the pre-sintered material. Based on this, the present application can regulate d1 by regulating the content of the second precursor material in the pre-sintered material.
[0063] The present application has no particular restrictions on the method of regulating the Dv50 of the positive electrode material, as long as the purpose of the present application can be achieved. For example, the Dv50 of the positive electrode material generally increases with the increase of the content of the second precursor material in the pre-sintered material. Based on this, the present application can regulate the Dv50 of the positive electrode material by regulating the content of the second precursor material in the pre-sintered material.
[0064] The present application also provides a battery, comprising the positive electrode sheet described in any of the above embodiments.
[0065] In the present application, the positive electrode material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode material layer can be arranged in a partial area of one surface of the positive electrode current collector, or in the entire area of one surface of the positive electrode current collector. In the present application, there is no special restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.
[0066] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of one surface of the negative electrode collector, or in the entire area of one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.
[0067] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.
[0068] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.
[0069] The lithium-ion battery of the present application also includes a diaphragm. The present application has no particular restrictions on the diaphragm, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0070] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, after mixing at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) according to a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, add lithium salt to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate.
[0071] The present application has no particular restrictions on the concentration of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. Taking LiPF6 as an example, the concentration of LiPF6 in the electrolyte is 5wt% to 25wt%, for example, the concentration of LiPF6 is 5wt%, 10wt%, 11wt%, 12wt%, 12.5wt%, 15wt%, 20wt% or 25wt%.
[0072] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.
[0073] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.
[0074] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.
[0075] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.
[0076] The electrical equipment of the present application may include but is not limited to: containers, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0077] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.
[0078] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0079] See also Figure 4 , Figure 4 A schematic diagram of a commercial energy storage system 400 according to an embodiment of the present application. Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.
[0080] The present application provides a commercial energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.
[0081] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0082] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.
[0083] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.
[0084] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 includes a single cell, the single cell may be at least one of a cylindrical battery, a square battery, and the like.
[0085] Example
[0086] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.
[0087] Example 1
[0088] <Preparation of positive electrode sheet>
[0089] <Preparation of the First Precursor Material>
[0090] According to LiFe 0.99 Ti 0.01 The required stoichiometric ratio in PO4 / C is obtained by weighing ferrous oxalate as an iron source, ammonium dihydrogen phosphate as a phosphorus source, lithium carbonate as a lithium source, titanium dioxide as a titanium source and glucose as a carbon source, and uniformly mixing them on a ball mill. Then, an appropriate amount of pure water is added as a dispersant, and then high-energy ball milling is performed. The ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 2000r / min, and the ball milling time is 20h; the material after high-energy ball milling is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a granular powder; the granular powder is placed in a vacuum atmosphere sintering furnace for the first sintering treatment, the protective atmosphere is nitrogen, the sintering temperature is 400℃, and the sintering time is 8h. After ball milling and crushing, the first precursor material is obtained.
[0091] <Preparation of Second Precursor Material>
[0092] According to LiFe 0.99 Ti 0.01The iron source ferrous oxalate, the phosphorus source lithium dihydrogen phosphate, the lithium source lithium carbonate, the titanium source titanium tetrachloride and the carbon source glucose are weighed in the required stoichiometric ratio of PO4 / C, and mixed to obtain a mixed metal salt solution; a strong base solution is prepared as a precipitant solution, and ammonia water is prepared as a complexing agent solution; wherein the molar concentration of titanium in the mixed metal salt solution is 0.5 mol / L, the strong base solution is a sodium hydroxide solution with a molar concentration of 1 mol / L, and the molar concentration of ammonia water is 1 mol / L; the mixed metal salt solution, complexing agent solution and precipitant solution prepared above are placed in a reactor, stirred continuously, the pH value of the reaction liquid is maintained at 9, the reaction temperature is 200°C, the reaction time is 10 hours, and the second precursor material is obtained by precipitation chemical reaction synthesis, and after solid-liquid separation, washing and drying.
[0093] <Preparation of positive electrode material>
[0094] The prepared first precursor material and the second precursor material are mixed to obtain a pre-burned material, wherein the content of the second precursor material in the pre-burned material is 10wt%; the pre-burned material is then placed in a vacuum atmosphere sintering furnace for a second sintering treatment, and then crushed to obtain a positive electrode material, wherein the protective atmosphere is nitrogen, the sintering temperature of the second sintering treatment is 700°C, and the sintering time is 10h.
[0095] <Preparation of positive electrode material layer>
[0096] The prepared positive electrode material, binder PVDF, and conductive carbon black (Super-P) are mixed in a mass ratio of 95:3:2, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 50wt%, and stirred evenly. Then, the positive electrode slurry is evenly coated on one surface of a positive electrode collector with a thickness of 10μm, dried at 85°C, and then the above steps are repeated on the other surface of the positive electrode sheet. After rolling, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained, and the single-side thickness of the positive electrode material layer is 100μm.
[0097] <Preparation of negative electrode sheet>
[0098] The negative electrode materials artificial graphite, conductive carbon black (Super-P) and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 95:2.5:2.5, deionized water was added, and a negative electrode slurry with a solid content of 60wt% was prepared and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, dried at 150℃, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode material layer coated on both sides was obtained, and the thickness of the negative electrode material layer on one side was 70μm.
[0099] <Preparation of Electrolyte>
[0100] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1, dissolved and stirred, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte solution, wherein the concentration of LiPF6 in the electrolyte solution was 12.5wt%.
[0101] <Preparation of Separator>
[0102] A polyethylene (PE) porous polymer film with a thickness of 16 μm was used as the separator.
[0103] <Assembly of lithium-ion batteries>
[0104] The prepared positive electrode sheet and negative electrode sheet are respectively placed in a press for pressing, and then a puncher is used to cut out a circular positive electrode sheet with a diameter of 15 mm and a circular negative electrode sheet with a diameter of 18 mm respectively; then the circular positive electrode sheet, the diaphragm and the circular negative electrode sheet are stacked in order, so that the diaphragm is placed between the circular positive electrode sheet and the circular negative electrode sheet to play an isolating role, and then the prepared electrolyte is injected to assemble into a lithium-ion battery.
[0105] Embodiment 2 to Embodiment 5
[0106] Except that in <Preparation of positive electrode material>, the content of the second precursor material in the pre-sintered material is adjusted according to Table 1, the rest is the same as Example 1.
[0107] Embodiment 6 to Embodiment 10
[0108] Except that the sintering temperature of the second sintering treatment was adjusted according to Table 1 in <Preparation of Positive Electrode Material>, the rest was the same as Example 1.
[0109] Example 11 to Example 15
[0110] Except that the sintering time of the second sintering treatment was adjusted according to Table 1 in <Preparation of Positive Electrode Material>, the rest was the same as Example 1.
[0111] Example 16
[0112] In addition to the steps of <Preparation of the First Precursor Material> and <Preparation of the Second Precursor Material>, according to LiFe 0.98 Ti 0.02 Except for weighing each raw material according to the stoichiometric ratio required in PO4 / C, the rest is the same as Example 1.
[0113] Embodiment 17
[0114] In addition to the steps of <Preparation of the First Precursor Material> and <Preparation of the Second Precursor Material>, according to LiFe 0.97 Ti 0.03Except for weighing each raw material according to the stoichiometric ratio required in PO4 / C, the rest is the same as Example 1.
[0115] Embodiment 18
[0116] In addition to the steps of <Preparation of the First Precursor Material> and <Preparation of the Second Precursor Material>, according to LiFe 0.96 Ti 0.04 Except for weighing each raw material according to the stoichiometric ratio required in PO4 / C, the rest is the same as Example 1.
[0117] Embodiment 19
[0118] In addition to the steps of <Preparation of the First Precursor Material> and <Preparation of the Second Precursor Material>, according to LiFe 0.95 Ti 0.05 Except for weighing each raw material according to the stoichiometric ratio required in PO4 / C, the rest is the same as Example 1.
[0119] Comparative Example 1
[0120] Except that in <Preparation of positive electrode material>, the pre-sintered material contains only the first precursor material but not the second precursor material, the rest is the same as Example 1.
[0121] Table 1: Relevant preparation parameters of each embodiment and comparative example
[0122]
[0123]
[0124] In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0125] Test methods and equipment:
[0126] Test of the ratio of the surface area of the second particle to the area of the largest cross section:
[0127] An optical 3D surface profiler (model VR-6000, resolution 0.1 μm) was used to accurately measure the three-dimensional surface morphology of 100 second particles in the positive electrode material, and the surface area and the area of the maximum cross section of each second particle were calculated simultaneously. Then, the sum of the surface area and the sum of the area of the maximum cross section of the 100 second particles were counted and recorded as S 1总 and S 2总 , then the ratio of the surface area of the second particle to the area of the largest cross section of the second particle is A = S 1总 / S 2总 .
[0128] Average particle size test of the third particle on the surface of the second particle:
[0129] A 3k-fold area was photographed under a scanning electron microscope (SEM), 100 second particles were randomly selected, the third particles attached to the surface of the particles were calculated, the particle size of the third particles was tested using ImageJ graphic testing software, and then the average value was calculated.
[0130] Cathode material particle size distribution test:
[0131] The particle size distribution of the positive electrode material was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method (GB / T19077-2016), thereby measuring the Dv50 of the positive electrode material.
[0132] Positive electrode elongation test:
[0133] like Figure 5 As shown, illustratively, the positive electrode sheet includes a positive electrode current collector 11, a first positive electrode material layer 12, and a second positive electrode material layer 13. The surface of the first positive electrode material layer 12 or the surface of the second positive electrode material layer 13 before rolling is marked with points A and B, and L1 is the distance between points A and B before the positive electrode sheet is rolled; after rolling by the roller 40, the positive electrode sheet will be extended along its length direction, and the distance between points A and B will be elongated, that is, the distance from A' to B', recorded as L2. The elongation rate of the sheet is calculated as: (L2-L1) / L1×100%.
[0134] Rate performance test:
[0135] The test temperature is 25°C. The lithium-ion battery is charged to 3.65V at a rate of 0.1 (C), and then discharged to 2.5V at a rate of 0.1C. The 0.1C discharge capacity is recorded in mAh / g.
[0136] Table 2: Performance data of various embodiments and comparative examples
[0137]
[0138]
[0139] It can be seen from Examples 1 to 19 and Comparative Example 1 that the elongation of the positive electrode sheet of Comparative Example 1 is relatively high and the 0.1C discharge capacity is relatively low. This may be because the positive electrode material of Comparative Example 1 does not have the morphology and structure of the positive electrode material of the present application, resulting in difficulty in using the second particles with a step-like structure to hinder the displacement and deformation of the positive electrode material particles when the positive electrode sheet is under pressure, and difficulty in effectively infiltrating the electrolyte into the interior of the positive electrode material particles, affecting the capacity of the positive electrode material; while the positive electrode sheet of the present application exhibits a low elongation, and the lithium-ion battery exhibits excellent capacity performance.
[0140] The content of the second precursor material in the pre-sintered material, the sintering temperature and sintering time of the second sintering treatment, and the content of the doping element (such as Ti) in the positive electrode material usually also have an impact on the performance of the positive electrode sheet. It can also be seen from Examples 1 to 19 that, on the basis of the positive electrode material having the structural characteristics of the present application, by regulating the above-mentioned preparation parameters within the scope of the present application, it is beneficial to obtain a lithium-ion battery with low elongation and high capacity performance.
[0141] Figure 6 This is the SEM image of the positive electrode material of Example 1 (magnification is 10,000 times), Figure 7 This is a SEM image of the positive electrode material of Example 1 (magnification is 30,000 times). Figure 6 and Figure 7 It can be seen that the second particles (i.e. the secondary particles with darker color and larger size in the figure) include multiple step-like structures with decreasing height, and the step-like structures have gaps, some of which are located at the fusion interface of the primary particles, and some are located at the junction of adjacent step-like structures; and, the surface of the second particles is also attached with first particles with relatively smaller particle size (i.e. the small particles with brighter color in the figure), and these first particles belong to primary particles.
[0142] Figure 8 This is the SEM image of the positive electrode material of Comparative Example 1 (magnification is 10,000 times), Fig. 9 This is the SEM image of the positive electrode material of Comparative Example 1 (magnification is 30,000 times). Figure 8 and Fig. 9 It can be seen that the positive electrode material particles have an ellipsoidal structure and do not have a step-like structure with a decreasing height trend.
[0143] The above is a detailed introduction to a positive electrode plate, a battery, an energy storage device and an electrical equipment disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A positive electrode sheet, characterized in that: A positive electrode current collector is included, wherein at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, the positive electrode material includes a first particle and a second particle, the second particle is a secondary particle formed by a third particle, and the first particle and the third particle are primary particles; Wherein, along the longest diameter of the second particle and in the direction away from the center of the second particle, the third particles located on the surface of the second particle form a plurality of step-like structures with decreasing height, and the plurality of step-like structures have gaps; A ratio of a surface area of the second particle to an area of a maximum cross section of the second particle is A, and 3≤A≤10.
2. The positive electrode sheet according to claim 1, characterized in that: The average particle size of the third particles located on the surface of the second particles is d1, and 1 μm≤d1≤3 μm.
3. The positive electrode sheet according to claim 1, characterized in that: The Dv50 of the positive electrode material is 1 μm to 3 μm.
4. The positive electrode sheet according to claim 1, characterized in that: One of the step-like structures is formed by fusion of a plurality of the third particles, and the gap is located at the fusion interface.
5. The positive electrode sheet according to claim 1, characterized in that: The gap is located at the junction of adjacent step-shaped structures.
6. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material has the chemical formula LiFe x Ti y PO4 / C, x+y=1, and 0<y≤0.
05.
7. The positive electrode sheet according to claim 1, characterized in that: The elongation rate of the positive electrode sheet is 0.5% to 2.3%.
8. A battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 1 to 7.
9. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 8, wherein the battery is accommodated in the casing.
10. An electrical device, characterized in that: It includes the energy storage device as described in claim 9, and the energy storage device supplies power to the electrical equipment.
Citation Information
Patent Citations
Cathode active material for lithium secondary battery and lithium secondary battery including same
CN111656585A
Positive pole piece, battery, energy storage device and electric equipment
CN118983395A
Positive electrode active materials for secondary battery and secondary battery comprising the same
US20180254511A1
Lithium ion secondary battery positive electrode material, lithium ion secondary battery positive electrode and lithium ion secondary battery that use same, and method for manufacturing lithium ion secondary battery positive electrode material
WO2016006557A1